Exploring the effects of mental and muscular fatigue in soccer players` performance - Coutinho, D.; Gonçalves, B.; Wong, D. P.; Travassos, B.; Coutts, A. J.; Sampaio, J. (Human Movement Science, 2018)
This study examined the effects of induced mental and muscular fatigue on soccer players` physical activity profile and collective behavior during small-sided games (SSG). Ten youth soccer players performed a 5vs5 SSG under three conditions: a) control, playing without any previous activity; b) muscular fatigue, playing after performing a repeated change-of-direction task; c) mental fatigue, playing after completing a 30 min Stroop color-word task. Players` positional data was used to compute time-motion and tactical-related variables. The muscular fatigue condition resulted in lower distances covered in high speeds (~27%, 0.3;±0.5) than the control condition. From the tactical perspective, the muscular fatigue condition resulted in lower distance between dyads and players spent ~7% more time synchronized in longitudinal displacements than the control condition (0.3;±0.3). Additionally, players spent ~14% more time synchronized with muscular fatigue than with mental fatigue (0.7;±0.3). The mental fatigue condition resulted in a very likely more predictable pattern in the distance between dyads than in muscular fatigue condition (0.4;±0.2). Also, the mental fatigue possibly decreased the teams` stretch index when compared with control (0.2;±0.3) and likely increased compared with muscular fatigue (0.5;±0.5). The better levels of longitudinal synchronization after muscular fatigue, might suggest the usage of tactical-related tasks after intense exercise bouts. The lower physical performance and time spent longitudinally synchronized after mental fatigue, should alert to consider this variable before matches or training activities that aim to improve collective behavior. AUTORREFERAT